Application of the Weighted Product Method to Determine House Renovation Assistance in Pringsewu Regency - Ponidi Ponidi; Riki Renaldo; Siti Mukodimah; Satria Abadi (Tech-E, 2021)
The challenge faced by local governments in implementing house renovation assistance is determining which residents are eligible to receive house renovation assistance. This problem can be overcome by creating an effective and efficient assessment system for receiving house renovation assistance. By using the Weighted Product (WP) method, it is hoped that it can help simplify and speed up the performance of local governments in selecting the recipients of house renovation assistance. The function of this method is to determine the weight value for each alternative and the criteria having been determined. From the analysis of the manual system using 9 criteria/indicators, the result is that prospective recipients who have a vulnerable value of 0.03 to 0.04 are more worthy of priority for house renovation assistance. If the vulnerable value is below 0.029, the prospective beneficiaries will be reviewed for the next year's RTLH program